2018
DOI: 10.1140/epjc/s10052-017-5476-3
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic quantum motion of spin-0 particles under the influence of noninertial effects in the cosmic string spacetime

Abstract: We study solutions for the Klein-Gordon equation with vector and scalar potentials of the Coulomb types under the influence of noninertial effects in the cosmic string spacetime. We also investigate a quantum particle described by the Klein-Gordon oscillator in the background spacetime generated by a cosmic string. An important result obtained is that the noninertial effects restrict the physical region of the spacetime where the particle can be placed. In addition, we show that these potentials can form bound… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 63 publications
7
91
0
Order By: Relevance
“…For B = 0 and χ = 0 we have relativistic energy levels of a scalar field subject to the Klein-Gordon oscillator in a uniformly rotating frame in the spacetime with a screw dislocation; for B = 0 and χ = 0 we have relativistic energy levels of a charged scalar field subject to the Klein-Gordon oscillator in a uniformly rotating frame subject to the Aharonov-Bohm effect in the Minkowski spacetime; for B = χ = 0 we recover the result obtained in the Ref. [26] without cosmic string.…”
Section: Particular Casesupporting
confidence: 81%
See 1 more Smart Citation
“…For B = 0 and χ = 0 we have relativistic energy levels of a scalar field subject to the Klein-Gordon oscillator in a uniformly rotating frame in the spacetime with a screw dislocation; for B = 0 and χ = 0 we have relativistic energy levels of a charged scalar field subject to the Klein-Gordon oscillator in a uniformly rotating frame subject to the Aharonov-Bohm effect in the Minkowski spacetime; for B = χ = 0 we recover the result obtained in the Ref. [26] without cosmic string.…”
Section: Particular Casesupporting
confidence: 81%
“…In an analysis by Landau and Lifshitz on the effects of rotation in the Minkowski spacetime with cylindrical symmetry, they showed that the radial coordinate becomes restricted in an interval, where this restriction is an effect directly related to the uniform rotation [21]. This restriction from the effects of uniform rotation has been widely used for studies in a relativistic quantum mechanics system, for example, in a Dirac particle [22], in a relativistic Landau-He-McKellar-Wilkens quantization [23], on the Dirac oscillator [24], on a scalar field in the spacetime with space-like dislocation and in the spacetime with a spiral dislocation [6], on the quantum dynamics of scalar bosons [25], in the relativistic quantum motion of spin-0 particles under in the cosmic string spacetime [26], in the Duffin-Kemmer-Petiau equation with magnetic cosmic string background [27]. In the nonrelativistic case, this restriction has been studied in a Dirac particle in the spacetime with a screw dislocation [16] and on nonrelativistic topological quantum scattering [28].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we investigate the above relativistic quantum system described by the Klein-Gordon oscillator subject to a Cornell-type scalar potential in the presence of external fields including an internal magnetic flux field. A scalar potential is included into the systems by modifying the mass m ⟶ m + SðrÞ which is called a position-dependent mass system in the relativistic quantum systems (see, e.g., [5,6,8,28,30,31,42,46,[52][53][54][55][56][57][58][59][60][61][62]).…”
Section: 2mentioning
confidence: 99%
“…Thus, the KG equation with interactions (the most general Lorentz structure) consists in vectors (A µ and X µ ), and scalar (V s ) potentials. Scalar particles in the background space-time generated by a cosmic string are very interesting systems that have been studied extensively in the literature in recent years [15][16][17][18][19][20]. A natural question arises, whether the presence of such kind of topological defect can also influence the behavior of scattering states and bound states of a given quantum system.…”
Section: Introductionmentioning
confidence: 99%